The Effect of Product Quality and Price on Purchase Decisions of Thrift Shop Products at Cimol Market, Gedebage, Bandung City - Febbiolla Tamara Putri; Sri Astuti Pratminingsih (International Journal Labs, 2026)
This study aims to analyze the influence of product quality and price on purchase decisions for thrift shop products at Cimol Gedebage Market, Bandung City. The research method used is a quantitative approach with survey methods and an associative descriptive research design. The research sample amounted to 316 consumers who made purchases at Cimol Gedebage Market, selected through convenience sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that product quality had a regression coefficient of 0.294 with a significance value of 0.00 () and -count of 8.111 > -table of 1.97, which indicates that product quality has a positive and significant effect on purchase decisions. Price had a regression coefficient of 0.424 with a significance value of 0.00 () and -calculated value of 11.556 > -table of 1.97, which indicates that price has a positive and significant effect on purchase decisions. Simultaneously, product quality and price had an -value of 69.256 > -table of 3.027 with a significance of 0.000 (), which indicates that the two variables together have a significant effect on purchase decisions. The coefficient of determination () showed that 30.2% of purchase decisions could be explained by product quality and price, while 69.8% were explained by other variables not included in the study. These findings provide actionable recommendations for thrift shop entrepreneurs to optimize their value proposition and inform government policies on balancing consumer protection with industry sustainability.